Faktor-Faktor yang Berhubungan dengan Kejadian Saluran Pernapasan Akut (Ispa) Balita di Wilayah Kerja Puskesmas Naibonat Kabupaten Kupang - Yermi A. Suek; Indriati A. Tedju Hinga; Deviarbi Sakke Tira (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Acute respiratory tract infection is a health problem in the world which is the main cause of morbidity and death in children under five years old (toddlers). Acute respiratory infections usually attacks the respiratory system from the upper respiratory system to the lower respiratory tract and has an incubation period of 14 days. This study aims to determine the factors associated with the incidence of ARI in toddlres in the Naibonat community health center working area. This type research is an analytical survey with a cross sectional reseach design. The simple consists of 92 popple with random sampling technique. Data analysis uses univariate and bivariate analysis with the chi-square test with a confidence level of p=0.005. The results of the study showed that factors related to ARI were maternal knowledge (p=0.002), nutritional status (p=0.004), smoking habits at home (p=0.005), while factors that were not related to the ocurrance of ARI were immunization status (p=0.847). Therefore, parents have an important role in efforts to prevent ARI disease by participating in socialization activities related to preventing ARI in toddlers, and for the public not to smoke carelessly in the home environment because the dangers of active smoking greatly affect toddlers in that environment.